The Phenotype Paradox: Lessons From Natural Transcriptome Evolution on How to Engineer Plants - Law, Justin; Ng, Kangbo; Windram, Oliver P. F. (Frontiers in Plant Science, 2020)
Plants have evolved genome complexity through iterative rounds of single gene and whole genome duplication. This has led to substantial expansion in transcription factor numbers following preferential retention and subsequent functional divergence of these regulatory genes. Here we review how this simple evolutionary network rewiring process, regulatory gene duplication followed by functional divergence, can be used to inspire synthetic biology approaches that seek to develop novel phenotypic variation for future trait based breeding programs in plants.